Efektivitas Monitoring Kesehatan Pasien Pengidap Penyakit Tidak Menular di Kajor Kulon Selopamioro Imogiri Bantul - Harahap, Feby Nur Alyani; Yebi, Saffana Racho Mauluda; Pradhana, Muhamad Ilham Satya; Rifa’i, Putri Fadia; Alfiani, Dhea Fita; Muna, Wildan Syithrul; Ayu, Yuniarti Mega; Putri, Zahra Saphira; Prayata, Kenzie Wistara; Fahrezy, Ergi Ahmad; Widayati, Aris (Universitas Muhammadiyah Yogyakarta, 2025)
Non-communicable diseases (NCDs) are the leading cause of death globally, with 41 million deaths each year. Non-communicable diseases are caused by a combination of modifiable and non- modifiable risk factors, including modern lifestyles that influence diet and smoking habits. In Kajor Kulon, Selopamioro, Imogiri, Bantul, D.I.Yogyakarta, people tend to practice unhealthy lifestyles such as consumption of foods high in sugar, salt and saturated fat, which contribute to the high prevalence of non-communicable diseases, including hypertension and diabetes. Therefore, this community service program aims to increase community awareness of NCDs through socialisation, screening, and health monitoring. The activity was conducted in February 2025, involving 75 high-risk and elderly participants. The method used in this approach was socialisation with material presentation on hypertension, followed by free health screening that included blood pressure, blood sugar, and cholesterol checks. Monitoring was conducted periodically for four families with NCDs. Monitoring results showed a decrease in blood pressure in participants, demonstrating the effectiveness of the programme in increasing awareness and adherence to a healthy lifestyle. Education on the dangers of NCDs and the importance of regular health check-ups proved to increase community awareness. Family support and a good understanding of health play an important role in controlling NCDs. This study emphasises the need for prevention programmes and continuous education to reduce the risk of NCDs in the community, as well as the importance of the government's role in providing affordable health services. Thus, collaborative efforts between the community, government and health institutions are needed to improve the quality of life and health of the community in Kajor Kulon. Through this approach, it is hoped that a healthier and more sustainable environment can be created for future generations.